Simpler Reference-Plane-Invariant Method for Permittivity Extraction of Medium- or Low-Loss Dielectric Samples Using One-Port Measurements - Ugur Cem Hasar; Husain Ali; Yunus Kaya; Ivaylo Stoyanov (IEEE Access)
A microwave method is devised to extract relative complex permittivity ( $ε _{r}$ ) of medium- or low-loss dielectric samples. It is simpler, non-iterative, reference-plane-invariant (RPI), and applicable for one-port waveguide measurements with short-circuit termination only. Besides, since it uses short-circuit termination reflection-only measurements, it is free from Fabry-Pérot resonances. Permittivity measurements of polyvinyl chloride (PVC) and polypropylene (PP) are performed at X-band ( $8.2-12.4$ GHz) to examine the performance of the proposed method considering different scenarios involving inaccurate information of sample location in the cell and inaccurate knowledge of the sample thickness. Repeatability analysis is carried out to analyze the performance of the proposed method against other similar methods in the literature.